(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Regularized regression techniques such as the least absolute shrinkage and selection operator (LASSO), elastic-net, and the type 1 and type 2 correlation adjusted elastic-net (CAEN1 and CAEN2 respectively) are used for simultaneously carrying out variable selection and estimation of coefficients in machine learning. Modified estimators based on the CAEN1 and CAEN2 are proposed in this study by rescaling the estimates to undo the double shrinkage incurred due to the application of two penalties. The scale factors are derived by decomposing the correlation matrix of the predictors. The derived scale factors, which depend on the magnitude of correlations among the predictors, ensure that the elastic-net is included as a special case. Estimation is carried out using a robust worst-case quadratic solver algorithm. Simulations show that the proposed estimators referred to as corrected correlation adjusted elastic-net (CCAEN1 and CCAEN2) perform competitively with the CAEN1, CAEN2, LASSO, and elastic-net in terms of variable selection, estimation and prediction accuracy with CCAEN1 yielding the best results when the number of predictors is more than the number of observations and CCAEN2 producing the best performance when there is grouping effect, where highly correlated predictors tend to be included in or excluded from the model together. Applications to two real-life datasets further demonstrate the advantage of the proposed methods for machine learning.